Pengaruh Profitabilitas, Likuiditas, Dan Solvabilitas Terhadap Harga Saham Perusahaan Subsektor Telekomunikasi Yang Terdaftar Di BEI - Kusviana, Fika; Merlyana Dwinda Yanthi (LPPM POLITEKNIK LP3I BANDUNG, 2024)
The company's financial performance can describe the high and low share prices. The aim of this research is to determine the effect of profitability, liquidity and solvency on share prices in telecommunications subsector companies listed on the IDX in 2018-2021. The population used is telecommunications subsector companies registered on the IDX that meet the required criteria. The data source uses secondary data in the form of financial reports obtained from the official BEI website. This research uses descriptive statistical analysis test techniques, classical assumption tests, multiple linear regression analysis, t test, and f test which can prove the hypothesis assisted by SPSS 26 software. The results of this research show simultaneously (F Test) the three independent variables, namely profitability which is measured using Return On Assets and Return On Equity, liquidity which is measured using the CR and QR, and solvency which is measured using the Debt to Assets Ratio and Debt to Equity Ratio have an influence on stock prices. Partially (T Test) shows that the CR and QR have an effect on stock prices, while the other variables, namely Return On Assets, Return On Equity, Debt to Assets Ratio, and Debt to Equity Ratio have no effect on stock prices.